An Assessment of Some Meristic and Metric Characteristics and Biological Indices of the Introduced Largemouth Bass (Micropterus salmoides) in Pantabangan Reservior, Nueva Ecija, Philippines - Mendoza, Gerondina C.; Vigilia, Erriz Gio R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study was conducted to characterize the invasive largemouth bass in Pantabangan Reservoir, Nueva Ecija in terms of meristic, metric and some biological indices. This study aimed to provide critical information on the size composition, length and weight relationship, body condition, sex ratio, stomach fullness and content, and other biological indices. Samples of largemouth bass were collected through the aid of commissioned fishers and subjected to meristic and biometric assessments. The data were consolidated and analyzed using descriptive statistics and simple linear regression. Results revealed some similarities with previous studies in terms of dorsal spine and rays and lateral line scales. Also, the biometric characteristics were found to be within the commonly reported range. The established model for the length and weight of fish showed high level of significance (p<0.01). As to condition factor, the range of the computed value of fish is 2.08 to 6.50 with a mean of 3.77. The range of hepatosomatic index of the fish is 0.1142 to 2.4623 with a mean of 1.0390 while gastrosomatic index recorded a range of 0.9132 to 6.8376 with a mean of 3.8560. Analysis of stomach content and food indices revealed that majority (61.00%) of fish samples exhibited empty stomachs. Furthermore, analysis of food items showed that the IRI percentage of fish is 88.96% while plant materials are negligible with IRI percentage of <10%. The obtained information showed some characteristics of the introduced fish; however, further assessment is imperative to have better insight of its status in the area.